"And Now I'm Just Different, but There's Nothing Actually Wrong With Me": Asexual Marginalization and Resistance. Issue 8 (3rd July 2017) - Gupta, Kristina
ABSTRACT: This article explores the relationship between contemporary asexual lives and compulsory sexuality, or the privileging of sexuality and the marginalizing of nonsexuality. Drawing on 30 in-depth interviews, I identify four ways the asexually identified individuals in this study saw themselves as affected by compulsory sexuality: pathologization, isolation, unwanted sex and relationship conflict, and the denial of epistemic authority. I also identify five ways these asexually identified individuals disrupted compulsory sexuality: adopting a language of difference and a capacity to describe asexuality; deemphasizing the importance of sexuality in human life; developing new types of nonsexual relationships; constituting asexuality as a sexual orientation or identity; and engaging in community building and outreach. I argue that some of these practices offer only a limited disruption of compulsory sexuality, but some of these practices pose a radical challenge to sexual norms by calling into question the widespread assumption that sexuality is a necessary part of human flourishing.